2020
DOI: 10.3389/fnhum.2020.00368
|View full text |Cite
|
Sign up to set email alerts
|

The Suppression of Taboo Word Spoonerisms Is Associated With Altered Medial Frontal Negativity: An ERP Study

Abstract: The constant internal monitoring of speech is a crucial feature to ensure the fairly error-free process of speech production. It has been argued that internal speech monitoring takes place through detection of conflict between different response options or "speech plans." Speech errors are thought to occur because two (or more) competing speech plans become activated, and the speaker is unable to inhibit the erroneous plan(s) prior to vocalization. A prime example for a speech plan that has to be suppressed is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 37 publications
3
16
1
Order By: Relevance
“…Altogether, 37 parapraxes were produced in this study, by 22 participants out of the 55. Although these 37 parapraxes represent about 1% of the experimental trials, 4 this number is comparable to other studies having replicated the SLIP technique (e.g., Hartsuiker et al, 2005 : 6.5%; Costa et al, 2006 : 1.9%; Severens et al, 2011 : 2.4%; Wagner-Altendorf et al, 2020 :0.7%). The proportion of partial spoonerisms in the total number of spoonerisms is high (more than 70%), but it is comparable to what has been reported in other studies (ca.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Altogether, 37 parapraxes were produced in this study, by 22 participants out of the 55. Although these 37 parapraxes represent about 1% of the experimental trials, 4 this number is comparable to other studies having replicated the SLIP technique (e.g., Hartsuiker et al, 2005 : 6.5%; Costa et al, 2006 : 1.9%; Severens et al, 2011 : 2.4%; Wagner-Altendorf et al, 2020 :0.7%). The proportion of partial spoonerisms in the total number of spoonerisms is high (more than 70%), but it is comparable to what has been reported in other studies (ca.…”
Section: Discussionsupporting
confidence: 75%
“…We propose that a number of slips, having passed the censorship of repression, and being readied to be discharged, i.e., executed or articulated, are halted at that stage: to cite Freud, (1915cite Freud, ( /1963, even if they were « capable of entering consciousness », they encountered « special resistance », and were censored from the system Cs; this particular resistance would then precisely be Motley et al's socially motivated prearticulatory editor. Severens et al (2011) found that, slightly after being confronted with the speech prompt, participants showed a larger negative brain wave in the taboo condition compared to the neutral condition, even if they produced no spoonerisms (see also Wagner-Altendorf et al, 2020). The authors interpreted this as evidence that taboo errors « are formed, detected, and corrected internally » and as « the first direct evidence that covert editing of speech exists » (Severens et al, 2011(Severens et al, , pp.…”
Section: What About Differences Between Neutral and Taboo Parapraxes?mentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of LFN, previous studies mainly reported that its amplitude is closely related to ambiguity or conflict. Larger negativity reflected the increased difficulty of processing the degree of ambiguity ( Astle et al, 2006 ; Mueller et al, 2007 ; Polezzi et al, 2008 ; Civai et al, 2020 ; Wagner-Altendorf et al, 2020 ). In the present study, when the rich proposed an unfair offer and were stingy, it might lead to a larger conflict with the social norm and cause the mismatch between a large amount of money owned and little money forgone.…”
Section: Discussionmentioning
confidence: 99%
“…Another component is the LFN, a negative component reaching peak amplitude around 400 ms post stimulus onset over frontal-central areas, which can index the degree of ambiguity or conflict ( Astle et al, 2006 ; Mueller et al, 2007 ; Polezzi et al, 2008 ; Civai et al, 2020 ; Wagner-Altendorf et al, 2020 ). In an object recognition task, Schendan and Kutas (2003) found that LFN was larger for those conditions in which objects were harder to identify.…”
Section: Introductionmentioning
confidence: 99%